2021
DOI: 10.3390/en14051367
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of CO Accumulation in the Headspace of the Bioreactor during Organic Waste Composting

Abstract: Advanced technologies call for composting indoors for minimized impact on the surrounding environment. However, enclosing compost piles inside halls may cause the accumulation of toxic pollutants, including carbon monoxide (CO). Thus, there is a need to assess the occupational risk to workers that can be exposed to CO concentrations > 300 ppm at the initial stage of the process. The objectives were to (1) develop a model of CO accumulation in the headspace of the bioreactor during organic waste composting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
1
11
0
1
Order By: Relevance
“…Taking into account the previously mentioned information on excessive CO production in bioreactors (both without ventilation and those opened to release process air), the safety aspect of composting plant employees becomes important. Having direct contact with composted waste, they are exposed to CO, the concentration of which significantly exceeds the acceptable generally limit values indicated by the WHO (Sobieraj et al, 2021). Therefore, it is necessary to develop personal protective equipment for workers currently working with the aerobic processing of organic waste in composting plants; however, it is also important to consider this problem in future facilities that interconnect composting plants with lines for further processing of the obtained CO, especially due to the intensification of this gas formation during the waste composting stage.…”
Section: Future Directions and Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Taking into account the previously mentioned information on excessive CO production in bioreactors (both without ventilation and those opened to release process air), the safety aspect of composting plant employees becomes important. Having direct contact with composted waste, they are exposed to CO, the concentration of which significantly exceeds the acceptable generally limit values indicated by the WHO (Sobieraj et al, 2021). Therefore, it is necessary to develop personal protective equipment for workers currently working with the aerobic processing of organic waste in composting plants; however, it is also important to consider this problem in future facilities that interconnect composting plants with lines for further processing of the obtained CO, especially due to the intensification of this gas formation during the waste composting stage.…”
Section: Future Directions and Limitationsmentioning
confidence: 96%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org its concentration can reach 3.2% (31,600 ppm) and 36.1% (360,000 ppm) for reactors with the daily release of accumulated gas and without ventilation, respectively (Sobieraj et al, 2021). High CO production in the initial stage of the process correlates with the temperature increase in the compost piles and shows the most significant increase in thermophilic conditions (Stegenta et al, 2019a).…”
Section: Composting Processmentioning
confidence: 99%
“…In developing the new software tool, the authors assumed that all available raw materials would be used as much as possible and also proposed a successful minimization of the production cost of the composting mixture. Sobieraj et al [122] created a model to predict carbon monoxide accumulation during composting of organic waste (dairy manure, grass clippings and pine sawdust) in a horizontal static bioreactor. The first-order kinetic model was used to describe carbon monoxide formation during the composting process.…”
Section: Household Waste Energy Transfer Balancementioning
confidence: 99%
“…The maximum methane potential and process kinetic is highly dependent on substrate, inoculum, equipment, and process conditions such as TS and pH. Deepanraj et al [52] analyzed the kinetic of biogas production from kitchen waste at different TS concentrations (5-15%) and pH (5)(6)(7)(8)(9). The result of Deepanraj et al [52] showed that first-order model kinetic (Gompertz model name by author) fit well to experimental data and had a determination coefficient > 0.994.…”
Section: Biomethane Production Kineticsmentioning
confidence: 99%